EFEK UKURAN WADAH SEMAI PADA PERTUMBUHAN AWAL BIBIT JAMBLANG (Syzygium cumini (L.) Skeels) - Levina Augusta Geraldine Pieter; Aris Sudomo (Jurnal Agroforestri Indonesia, 2021)
Java plum or also known as jambolana, jamblang, or duwet has many benefits such as natural dye, a source of natural antioxidants, anti-inflammatory, anti-cancer and as a medicine for diabetes. However, the cultivation technique is still not widely known in advance. The size of the plant pot affects the physiological and morphological properties of plants and also affects the mass production of seedlings. The purpose of this study was to determine the size of the polybag as the best seedling container for optimum jamblang’s growth. The study was conducted in a greenhouse using a completely randomized design (CRD). There are four sizes of polybag sizes were 10x15, 12x20, 15x25, and 20x30, each treatment using 50 plants so that a total of 200 seeds were used. Parameters measured were height, diameter, wet weight of roots and wet weight of stems and leaves of Jamblang seedlings. The Anova and DMRT were used for analysis using the SPSS.  The results showed that the polybag size significantly affected the seedlings height, root wet weight and wet weight of stems and leaves of seedlings (33.75 cm, 16.86gr, and 19.91gr respectively). For jamblang seedlings in this study, the polybag size that gave the highest yield was polybag with a size of 20x30.